How BNPL is reshaping the financial lives of Malaysian university students - UiTM, MITASA (Kesatuan Kakitangan Akademik UiTM (MITASA), 2025)
Buy now, pay later" (BNPL) is a individuals to purchase goods or services and pay for them over time. BNPL has gained popularity over time as a simpler, faster, and more accessible alternative to credit cards. It does not require a strong credit history or complex approval processes. In addition, the payment methods for BNPL are being split into instalments with no interest being charged if the deadlines are met.